Performance Analysis Of Vertical Axis Wind Turbine Blades Using Double Multiple Stream Tube Process - Badah, Muneer.R.; Mahmood , Yaseen.H. (Iraqi Journal of Science, 2022)
The interest in green energy in recent years is very noticeable, as this energy is a very important alternative that can replace fuel in many applications, most notably electric power generation, so work must be done to develop a form of this energy such as wind energy by working on the development of turbines. The DMST method provided by Qblade software is an integrated tool for making a simulation of a vertical axis wind turbine (VAWT). The simulation was carried out on vertical axis wind turbines, designing turbine blades according to symmetrical NACA0018, and calculating some parameters such as power, torque and power coefficient. It is found that this type of turbine can be improved by treating the blade edges that contribute to the turbine power loss, thus improving the turbine at low wind speeds.